Rancang Bangun Aplikasi Promosi Karyawan Berdasarkan Kompetensi Pada PT Memorandum Sejahtera - Efendi, Luvi; Amelia, Tan; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract:Memorandum newspaper headquartered in Kembang Jepun No.167-169 Street, Surabaya. Memorandum is a weekly newspaper company that stands on 10 November 1969 and has many years become a popular newspaper in the field of media information. Human resources is a source of competitive advantage and the key elements that are essential for success in achieving competing objectives. An individual employee increased position employee promotion will encourage human resources as a whole in increased productivity. Based on observations and interviews, the company experienced problems in the process of position employee promotion as well as items that are still considered in general and not detailed, although the company has the competency standards are structured, and the frequent occurrence of errors in perekapan as well as the calculation of assessment data as it is still done manually and the length of time required to run multiple processes in position employee promotion. For overcome these problems, then made an application solution Promotion of Employee Competence Based on PT. Memorandum Sejahtera. This application can shorten the process and the time taken is 25 days become 9 days at the stage of promotion of employees by way of doing automation such as data recording competence and perekapan results of promotion of employees (1 day), the performance assessment (7 days), analyzing assessment and reporting of assessment results promotion of employees (1 day). Keywords: Application, Position Employee Promotions, Competency Standards